If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2f + -8 = -7f + 27 Reorder the terms: -8 + -2f = -7f + 27 Reorder the terms: -8 + -2f = 27 + -7f Solving -8 + -2f = 27 + -7f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '7f' to each side of the equation. -8 + -2f + 7f = 27 + -7f + 7f Combine like terms: -2f + 7f = 5f -8 + 5f = 27 + -7f + 7f Combine like terms: -7f + 7f = 0 -8 + 5f = 27 + 0 -8 + 5f = 27 Add '8' to each side of the equation. -8 + 8 + 5f = 27 + 8 Combine like terms: -8 + 8 = 0 0 + 5f = 27 + 8 5f = 27 + 8 Combine like terms: 27 + 8 = 35 5f = 35 Divide each side by '5'. f = 7 Simplifying f = 7
| 2x+11=29 | | 7w+4-w=8w-2(w-2) | | 4n-5=3n+8 | | 2x+15=33 | | (5x+3)(4y-1)= | | 4m-2=5m+5-m | | 5y+12=32 | | 17-19y=-3+16y | | (3a-3f)(3a+2f)= | | 8y+5=8y-5 | | 15r=8r-56 | | 11-(6v+7)=-6v-4 | | 3x+12=5t+6 | | 6+3t=3t-14 | | -8-6(x+3)=2x-6x+5 | | -10-5x=10-10 | | 3x+16=32 | | 8(x+2)=40 | | -4+7(1-3m)=0 | | -y+2x=9 | | 3(x+2)=-x+30 | | [9(x+5)-7]+[4(x-12)+9]= | | 2.3x-0.11=0.8x+34.39 | | 3x-2(12)=-13 | | 3x-8=13-4p | | 5(2x-9)=7x-60 | | -9k+8k=0 | | 8.3x-25=4.9x+97.9 | | -1(y-8)=2(y+4) | | (30-2y)+3=y | | 3(y-2x)=2 | | 0.58+0.15y=4.78 |